A Study on the Effect of Housing on Parasitic Load of Nellore Lambs (Indian Journal of Animal Production and Management, 2024)
A study was carried out to find out the effect  of housing on Parasitic load of Nellore Jodipi lambs  under tropical environmental conditions. Thirty  weaned Nellore ram lambs of 3-4 months age were  selected based on body weight and randomly  divided into three groups of ten animals each. The  parasitic load i.e., Egg per gram (EPG) was  determined regularly at every month during entire  study period. The faecal egg count was performed  by a Mc Master technique. With regard to parasitic  load, the prevalence of parasites and eggs per gram  (EPG) count were significantly (P
Keywords: Nellore Jodipi lambs; Housing; Parasitic load; EPG